PELAKSANAAN KERJA PELAYANAN WORK FROM HOME DAN IMPLIKASINYA TERHADAP PENILAIAN PRODUKTIVITAS KERJA PEGAWAI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA KENDARI - Reski Melyana Melamba; Jamal Bake; Erni Qomariyah (Universitas Halu Oleo, 2021)
The implementation of work from home certainly has a positive and negative impact on employee work productivity, this paper provides a description of whether or not the work system needs to be continued after the pandemic ends or an evaluation is required considering the emergence of a deadly new type of covid 19 virus variant, it is very possible for government organizations to carry out WFH, this study aims to describe the implementation of work from home and explain its implications,The dimensions of feasibility, availability, speed of response, physical environment, data security, office equipment, and technical support have not been effective, whereas work supervision has been running quite effectively, if there are several employees who experience a decrease in work productivity while working from home, this is based on an assessment of the ability to carry out tasks, work enthusiasm, and motivation to develop oneself, as w workplace. compatible, domestic disturbances in households, the absence of standard operating procedures that touch on technical issues, operating hours restrictions, a lack of conducive communication between superiors and subordinates, and a growing mindset that work from home is perceived as only an appeal/temporary recommendation During an emergency,it is not a binding regulation